2019
DOI: 10.1111/ijlh.13083
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of Revohem FVIII chromogenic and Revohem FIX chromogenic in the CS‐5100 autoanalyser

Abstract: Introduction Chromogenic substrate assay (CSA) reagents Revohem™ FVIII and Revohem™ FIX are now available as in vitro diagnostic reagents for autoanalysers in Japan. In this study, we evaluated the performance of these reagents in the CS‐5100 automated coagulation analyser. Methods We assessed within‐run and between‐day imprecision, on‐board stability and frozen‐storage stability of Revohem FVIII and FIX. Sensitivity to lupus anticoagulant (LA) was examined using LA‐positive patient plasma. Correlations were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Additionally, we could not investigate variations in CSA reagents. Our previous study showed no significant differences between Revohem FVIII chromogenic and Siemens FVIII chromogenic kits, 20 supporting another previous study showing no consistent differences between the three most commonly used kits 27 . On the other hand, another study confirmed the presence of significant differences in FVIII:C Chr results between CSAs 28,29 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Additionally, we could not investigate variations in CSA reagents. Our previous study showed no significant differences between Revohem FVIII chromogenic and Siemens FVIII chromogenic kits, 20 supporting another previous study showing no consistent differences between the three most commonly used kits 27 . On the other hand, another study confirmed the presence of significant differences in FVIII:C Chr results between CSAs 28,29 .…”
Section: Discussionsupporting
confidence: 83%
“…One‐stage clotting assay for FVIII was carried out on a CS‐5100 analyser (Sysmex) according to the method described in a previous study, 20 with the following modifications. Fifteen microlitres of the plasma sample was diluted with 135 µL of Owren's veronal buffer (OVB; Sysmex).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of FIX activity is useful to ensure efficacy of treatment in several settings 1 and is commonly done by one‐stage or chromogenic FIX activity assay 2,3 . There are many different versions of one‐stage assay and at least 3 chromogenic assay kits 4‐7 . There may be clinically relevant differences between results of different FIX assays in FIX concentrates 8 and in haemophilia B patients before 9,10 and after infusion of concentrates 6 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 There are many different versions of one-stage assay and at least 3 chromogenic assay kits. [4][5][6][7] There may be clinically relevant differences between results of different FIX assays in FIX concentrates 8 and in haemophilia B patients before 9,10 and after infusion of concentrates. 6 There are particularly marked differences between results with different methods in the presence of extended half life concentrates.…”
Section: Introductionmentioning
confidence: 99%